Study on the effect of lithium nitrate in ionic conduction properties based alginate biopolymer electrolytes - Ahmad Faizrin, Fuzlin; Bakri, Hassan; Sahraoui, B.; Ahmad Salihin, Samsudin (Institute of Physics Publishing, 2019)
In this present work, the conduction properties of biopolymer electrolytes (BEs) based alginate incorporation with LiNO3 was studied. FTIR analysis showed there is complexation occurred when incorporation with LiNO3 via COO− group of alginate. The interaction between alginate and LiNO3 shown an improvement in ionic conductivity of BEs where was increased from 3.24 × 10–7 S cm−1 for un-doped sample and achieved optimum value at 1.14 × 10–4 S cm−1 for sample containing with 15 wt. % LiNO3. The prepared samples shown that it has thermally assisted when the temperature is increased and shown Arrhenius behavior. Deconvolution approached revealed that the present ionic conduction of BEs influenced by ionic mobility and diffusion coefficient.